2012
DOI: 10.1590/s0104-11692012000200016
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of pressure ulcers after the implementation of a prevention protocol

Abstract: Even in the present, pressure ulcers still represent a severe health problem, particularly in Intensive Care Units (ICU). This study assesses the implementation of a protocol to prevent pressure ulcers in ICU inpatients. This prospective, descriptive and exploratory study verifies the incidence of pressure ulcers following the implementation of a prevention protocol. Data were collected from April 17th to July 15th 2009. The incidence observed in this study (23.1%) was below that reported in a similar study de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
115
2
45

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(171 citation statements)
references
References 9 publications
8
115
2
45
Order By: Relevance
“…(15) The present study showed a calcaneal pressure ulcer incidence of 32% in patients admitted to the intensive care units of a public hospital, corroborating previous studies with reported incidences betwen 23,1% and 42.4%. (2,6,16,17) Another study of patients that were submeted a elective surgery the indices of pressure ulcer was 18,1%. (17) In terms of the days in which there was a greater incidence of pressure ulcer , results found a tendency toward development of pressure ulcer in the first two weeks of hospitalization, with higher incidence occurringbetween days 1-15, especially with in the first five days, with highest incidence in the first 48 hours.These findings were consistent with previous study results.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…(15) The present study showed a calcaneal pressure ulcer incidence of 32% in patients admitted to the intensive care units of a public hospital, corroborating previous studies with reported incidences betwen 23,1% and 42.4%. (2,6,16,17) Another study of patients that were submeted a elective surgery the indices of pressure ulcer was 18,1%. (17) In terms of the days in which there was a greater incidence of pressure ulcer , results found a tendency toward development of pressure ulcer in the first two weeks of hospitalization, with higher incidence occurringbetween days 1-15, especially with in the first five days, with highest incidence in the first 48 hours.These findings were consistent with previous study results.…”
Section: Discussionmentioning
confidence: 98%
“…(3) In Brazil, studies of pressure ulcers in the intensive care units (ICU) of university and public hospitals identified incidences that ranged between 19.2% and 44%. (4)(5)(6) Research conducted in the U.S. in sectors such as medical clinics, surgical, neurological, rehabilitation and intensive care units areas showed an overall incidence ranging from 3.5% to 33%. (7) This finding highlights the importance of scientific evidence on the effectiveness of prophylactic options such as transparent polyurethane film (TPF), from a perspective of evidence-based practice (EBP), since this technology is indicated for such use, despite the fact that studies about this technology are still scarce and no strong evidence exists to ensure an evidence-based, minimally invasive practice with a lower iatrogenic effect on hospitalized patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, one should take into account a study evaluating the risk for PU, in which there was a higher incidence of males (56.6%) in a population of patients hospitalized at a university hospital with a rate of 78.6 % of the subjects older than 60 years (19) .…”
Section: Discussionmentioning
confidence: 99%
“…Estudos sobre a ocorrência de UP são cada vez mais utilizados como ferramentas de refinamento das práticas de prevenção e capazes de avaliar a variação do número de indivíduos acometidos pelo problema, a qualidade do cuidado em saúde e a eficácia das iniciativas de prevenção. No Brasil, poucos estudos relatam essas iniciativas considerando o aspecto da qualidade institucional (7,8) . A investigação da prevalência constitui o primeiro passo para caracterizar a situação de forma quantitativa, podendo ser uma ferramenta utilizada em pesquisa epidemiológica ou em programas de melhoria de qualidade (1,2,7) .…”
Section: Introductionunclassified